A economia das compras governamentais em decorrência do pregão eletrônico – uma abordagem econométrica - Silva, Antonio Araújo da (2007)
The present dissertation addresses one of the most important themes in the area of public bids in Brazil, in this case, electronic bidding, created by law number 10.520/02 and regulated by decree number 5.450/05. The microeconomic theory of the structure of market and auctions shows that a larger number of competitors provides lower prices to buyers. Thus the objective of this work is to test this hypothesis and verify the main determining factors that make the final price of electronic bidding lower than the price estimated by public administration. In other words, there is an attempt to measure the impact of number of suppliers participating in the bidding and the number of bids made in the resulting economy offered to the public treasury in the City Hall in Fortaleza in 2006 through the use of electronic bidding. The study used data from the purchase list of Banco do Brasil in all electronic biddings in homologated cases done by the Fortaleza City Hall in 2006 -- a total of 141 biddings with a total of 448 bids. Two models of linear regression with cross data were used as never before to quantify the influence of the number of suppliers and bids in the discount obtained by the administration in several biddings. This was done with the use of econometric models estimated by the minimum squared method. The results showed that the effect of the number of suppliers in the average discount obtained by the municipality of Fortaleza is larger than the effect of the number of bids. It was also verified that the ideal situation for the administration is the interval of 11 to 15 suppliers, with an average obtained discount of 31.74%. Fortaleza City Hall had an average saving of 25% in biddings done in the year 2006, whereas the Federal Government obtained 14%. Through the study it was possible to verify that electronic bidding brings forth many advantages to public administration, such as, transparency, agility in purchases -- because average time spent is less -- and possibility of data quantification available in the world wide web, which also helped in the accomplishment of this dissertation. The inversion of phases in the public bidding process, already being in use by bidding makes the process much more agile. It also reduces government and supplier’s expenses. At the end of the work, a recommendation to the City Hall of Fortaleza is made for them to adopt measures for the improvement of municipal purchases.